Tinjauan Sistematik Terhadap Model Bisnis dan Inovasi Teknologi pada Start-up - M. Iqbal Zuqron; Jhon Veri (LPPM Universitas Buddhi Dharma, 2025)
This research aims to provide a systematic review of business model development and technological innovation in start-ups in the digital era. Using the Systematic Literature Review (SLR) method, this research analyzes relevant literature published between 2021 and 2024. The main focus of the research is to understand the impact of digital transformation on the performance of small and medium enterprises (SMEs) and how digital technology innovations, such as artificial intelligence (AI) ), blockchain, and big data, supporting entrepreneurial growth. The literature selection process involves tools such as Publish or Perish, Covidence, and VOSviewer to visually analyze bibliometric data. The research results show that digital technology integration can increase operational efficiency, accelerate business growth, and open up new opportunities in the market. Visualization using VOSviewer emphasizes the important role of AI in digital marketing innovation, strengthening brand identity, as well as efficient solutions to market challenges. The conclusions of this research provide strategic insights for entrepreneurs, investors and policy makers to support the sustainability and success of start-ups in Indonesia. This research also emphasizes the importance of innovative business models to create sustainable economic value and the relevance of digital transformation in strengthening the competitiveness of SMEs.